Astaxanthin rescues neuron loss and attenuates oxidative stress induced by amygdala kindling in adult rat hippocampus. (15th June 2015) - Lu, Yan; Xie, Tao; He, Xue-Xin; Mao, Zhuo-Feng; Jia, Li-Jing; Wang, Wei-Ping; Zhen, Jun-Li; Liu, Liang-Min
Highlights: ATX attenuated the neuron damage induced by amygdale kindling. ATX suppressed the oxidative damage and lipid peroxidation induced by amygdale kindling. ATX inhibited the translation of CytC release and caspase-3 activation induced by amygdale kindling. Abstract: Oxidative stress plays an important role in the neuronal damage induced by epilepsy. The present study assessed the possible neuroprotective effects of astaxanthin (ATX) on neuronal damage, in hippocampal CA3 neurons following amygdala kindling. Male Sprague–Dawley rats were chronically kindled in the amygdala and ATX or equal volume of vehicle was given by intraperitoneally. Twenty-four hours after the last stimulation, the rats were sacrificed by decapitation. Histopathological changes and the levels of reactive oxygen species (ROS), malondialdehyde (MDA) and reduced glutathione (GSH) were measured, cytosolic cytochrome c (CytC) and caspase-3 activities in the hippocampus were also recorded. We found extensive neuronal damage in the CA3 region in the kindling group, which was preceded by increases of ROS level and MDA concentration and was followed by caspase-3 activation and an increase in cytosolic CytC. Treatment with ATX markedly attenuated the neuronal damage. In addition, ATX significantly decreased ROS and MDA concentrations and increased GSH levels. Moreover, ATX suppressed the translation of CytC release and caspase-3 activation in hippocampus. Together, these results suggest that ATX protects against neuronal loss due to epilepsy in the rat hippocampus by attenuating oxidative damage, lipid peroxidation and inhibiting the mitochondrion-related apoptotic pathway.